Light therapy modulates serotonin levels and blood flow in women with headache. A preliminary study. Issue 1 (January 2016) - Tomaz de Magalhães, Miriam; Núñez, Silvia Cristina; Kato, Ilka Tiemy; Ribeiro, Martha Simões
In this study, we looked at the possible effects of low-level laser therapy (LLLT) on blood flow velocity, and serotonin (5-HT) and cholinesterase levels in patients with chronic headache associated with temporomandibular disorders (TMD). LLLT has been clinically applied over the past years with positive results in analgesia and without the report of any side effects. The understanding of biological mechanisms of action may improve clinical results and facilitate its indication. Ten patients presenting headache associated with TMD completed the study. An 830-nm infrared diode laser with power of 100 mW, exposure time of 34 s, and energy of 3.4 J was applied on the tender points of masseter and temporal muscle. Blood flow velocity was determined via ultrasound Doppler velocimetry before and after laser irradiation. The whole blood 5-HT and cholinesterase levels were evaluated three days before, immediately, and three days after laser irradiation. Pain score after treatment decreased to a score of 5.8 corresponding to 64% of pain reduction ( P  < 0.05). LLLT promoted a decrease in the blood flow velocity ( P  < 0.05). In addition, the 5-HT levels were significantly increased three days after LLLT ( P  < 0.05). The cholinesterase levels remained unchanged at the analyzed time points ( P  > 0.05). Our findings indicated that LLLT regulates blood flow in the temporal artery after irradiation and might control 5-HT levels in patients suffering with tension-type headache associated to TMD contributing to pain relief.